(Oxidation of VItamin A. Factors Affecting the Rate of Autoxidation of Vitamin A.) - Slamet Pardijanto, Muhammad (Balai Besar Industri Agro, 1988)
When vitamin A undergoes oxidation in fatty food, two possible types of oxidation should be considered. Firstly, there is a possibility for the vitamin A to react directly with oxygen. However, it is also possible to be oxidised by the products of autoxidation of the lipid. This work is set out to study the rate of autoxidation of vitamin A. It is shown that this process is relatively slow. The factors which influence the rate of autoxidation were also explored.Â